PERBANDINGAN KUALITAS HIDUP PASIEN SEBELUM DAN SETELAH PERCUTANEOUS CORONARY INTERVENTION (PCI) - Cicilia " Rahmawati; Safri " "; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research is to compare patient quality of life before and after Percutaneous Coronary Intervention (PCI). This research used comparative study design with retrospective. This Research done in Cardiologist outpatient of RSUD Arifin Achmad Pekanbaru, there was 58 patient PCI which was chosen by using Accidental Sampling technique by considering inclusion criteria. Measuring instrument used was a questionnaire that has been tested validity and reability. Analysis that was used is bivariate analysis with Wilcoxon. The average quality of life before PCI with result 23.95, while another for quality of life after PCI is 24.71. Result of this research showed that there is an increased quality of life after PCI. This research results show is a difference in quality of life before and after PCI with the result p value (0.003) < α (0.05). According to this research, the hospital are expected to health education related to PCI and efforts to improve the quality of life for patient PCI. Keyword: quality of life, Percutaneous Coronary Intervention (PCI).